Digital Receipts of Online Transactions in the Reconciliation Process and the Preparation of Financial Reports - Ferry Kosadi; Wajib Ginting; Vina Merliana (Journal of Indonesian Economy and Business (JIEB), 2021)
Introduction/Main Objectives: This research seeks to analyze the use of digital receipts and multi-platform e-commerces’ data integration and the influence they have on the process of reconciliation and the preparation of financial reports by micro, small, and medium-sized enterprises (MSMEs). Background Problems: The use of multi-platform online transactions requires the validation and conversion of the data, which can be an issue during the reconciliation process and the preparation of financial reports. The issue of the data’s integration is due to differences in the interfaces used for the multi-platform transactions and the MSMEs internal abilities. Novelty: The integration and treatment of online transactions via multi-platforms should an internal records or database for the MSMEs, the reconciliation process and preparing financial reports. Research Methods: This research uses a quantitative method with partial least squares structural equation modeling (PLS-SEM) analysis and descriptive analysis to reveal the reconciliation process and the conditions under which financial reports are prepared. Finding/Results: The problems of integrating data from various platforms into internal reports causes duplication of the internal reporting and a long reporting process and the chance of errors. The digital receipt is treated as proof of a manual transaction. Records’ duplication is a technical issue that causes delays in the processing time and reconciliation. None of the MSMEs have a machine-to-machine based (automized) reconciliation process. Conclusion: Transaction receipts from all the platforms affect the transactions’ recording, the reconciliation process, and the preparation of financial reports. Digital receipts provide high levels of confidence because of their completeness, accuracy, easiness, efficiency, simplicity, and suitability for use by MSMEs. The adoption of online sales and payments by MSMEs is highly effective, yet this has not been followed-up with the data’s integration into the reconciliation and accounting process for preparing financial reports.